Pengembangan Aplikasi Pengenalan Alat Musik Tradisional Sumbawa Untuk Melestarikan Kebudayaan - Aprianti, Ade Lilis; Esabella, Shinta (AMIK STIEKOM SUMATERA UTARA, 2024)
Most regions in Indonesia, including Sumbawa, have unique and distinctive traditional musical instruments. Traditional musical instruments are part of the cultural characteristics of a region, and function as the main means of reflecting the cultural heritage that has been passed down from generation to generation. Due to the lack of interest of the younger generation in getting to know customs and customs, many art studios have been closed or deactivated because there are no successors and the younger generation's interest in learning traditional Sumbawa musical instruments. Therefore, the author designed an application to introduce traditional Sumbawa musical instruments to preserve culture using qualitative data collection methods and eXtreme Programming methods as methods for software development. It is hoped that the development of this application can preserve Sumbawa culture and help the local government of Sumbawa Regency to introduce the cultural heritage of Tana Samawa to the local community, especially the younger generation, in order to maintain and preserve local cultural riches.